2021
DOI: 10.1136/bmjopen-2021-049522
|View full text |Cite
|
Sign up to set email alerts
|

Vocational interventions to help adults with long-term health conditions or disabilities gain and maintain paid work: an overview of systematic reviews

Abstract: ObjectiveTo conduct an overview of systematic reviews to examine the effectiveness of vocational interventions to help adults with long-term health conditions or disability gain and maintain new paid work and to analyse the spread and quality of evidence in this area.MethodsWe pre-published our protocol in PROSPERO (CRD42019132448). We searched Cochrane Database of Systematic Reviews, MEDLINE, EMBASE, PsycINFO, AMED, CINAHL, Proquest Dissertations and Theses database, NICE and Business Source Complete from inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Third, we relied on a network of IPS researchers who informed us of recent research. Fourth, we examined the reviews identified by Levack and Fadyl 46 …”
Section: Effectiveness Of Ipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we relied on a network of IPS researchers who informed us of recent research. Fourth, we examined the reviews identified by Levack and Fadyl 46 …”
Section: Effectiveness Of Ipsmentioning
confidence: 99%
“…One systematic compilation of 26 empirical reviews of employment interventions for people with a wide range of disabilities concluded that IPS studies comprised most of the available evidence and that, aside from employment programs for people with severe mental health conditions, "we found only very low-quality to low-quality evidence on vocational intervention for people with any other health condition." 46…”
Section: Effectiveness Of Ipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocational rehabilitation programs assist individuals in re-entering the workforce or adapting to new occupational roles post-amputation. These programs offer valuable support in career counselling, skill development, and workplace accommodations, ensuring that individuals can continue to pursue fulfilling and meaningful careers [ 62 ].…”
Section: Reviewmentioning
confidence: 99%